Sistem Pendukung Keputusan Budidaya Tanaman Cabai Berdasarkan Prediksi Curah Hujan - Hilal Imtiyaz; Barlian Henryranu Prasetio; Nurul Hidayat (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Abstract Chili is one of holticultura product wich is needed every day by Indonesian people. They use chili for spice in cooking. Chili supply not any time to meet demand. It causes price increases in accordance with the law of demand and supply. The surge in prices because of limited supplies occur every year. One of the problems that cause unavailability of supply throughout of year is chili crop failure cause chili cultivation is not good. pepper cultivation planning must consider the rainfall so that water for plants is available. Chili plants would not grow well if the plants lack of of water or if the water is too much. It will disturb chili growth, fertilization and crop becomes susceptible to pests. The main source off plants irrigation is rain. Knowledge of rainfall in the future will help farmers in cultivating planning. This research will discuss about decision support systems of chilli cultivation based on the rainfall prediction using simple linear regression method. Regression method used to predict the rainfall with modeling rainfall data in previous years. Based on the data the rainfall forecasts, system will recomanded best ways of pepper cultivation. Results of rainfall prediction using simple linear regression method has the accuracy rate of 91.6% which inluantial to the good of chili cultivation. Keywords: Decision Support Systems, Chili, Simple Linear Regression, Rainfall.